Economic, social and gender aspects of the international migration in Moldova - Dorin VACULOVSCHI; Elena VACULOVSCHI (Eastern European Journal of Regional Studies)
International labor migration is one of the most marked phenomenon that characterize the current situation on the Moldovan labor market. Geographical and gender distribution in labor migration is largely determined by the type of work that provide migrant workers. Women migrate to provide domestic and care services abroad, delegating in the same time their responsibilities in this area to other people, leads to the constitution of so-called global care chains. Migration with the purpose of study in Moldova is accompanied by a negative phenomenon, of the departure of highly qualified specialists. International migration of highly skilled labor, known as "brain drain"clearly evokes a loss of intellectual capital. Moldova continues to be characterized as an origin country of human beings trafficking, being at lesser extent a country of transit of human trafficking victims from NIS countries to Europe. The lack of some measures from the Government on “human capital loss” problem will essentially reduce the chances of exit from the crisis.